2017
DOI: 10.3390/nano7120417
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bacteria Associated with Wound Infection by Biocompatible Green Synthesized Gold Nanoparticles from South African Plant Extracts

Abstract: Unlike conventional physical and chemical methods, the biogenic synthesis of gold nanoparticles (GNPs) is considered a green and non-toxic approach to produce biocompatible GNPs that can be utilized in various biomedical applications. This can be achieved by using plant-derived phytochemicals to reduce gold salt into GNPs. Several green synthesized GNPs have been shown to have antibacterial effects, which can be applied in wound dressings to prevent wound infections. Therefore, the aim of this study is to synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 69 publications
(85 reference statements)
7
53
0
Order By: Relevance
“…The selectivity of M TMR-AuNPs (25 °C) and M TMSB-AuNPs (70 °C) on the three cancer (MCF, HepG2 and Caco-2) cells was within the selectivity index range from 6.5 to 82.2. The results corroborate with the finding of [ 53 ] that showed that biogenic AuNPs synthesized from the South African Galenia africana and Hypoxis hemerocallidea plants extracts showed that there was no significant reduction in viability of KMST-6 cell after 24 h treatment with AuNPs with concentrations up to 32 nM [ 16 ]. The same finding has been demonstrated by Patra [ 67 ], showing that AuNPs were non-toxic towards Hek293T cells.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The selectivity of M TMR-AuNPs (25 °C) and M TMSB-AuNPs (70 °C) on the three cancer (MCF, HepG2 and Caco-2) cells was within the selectivity index range from 6.5 to 82.2. The results corroborate with the finding of [ 53 ] that showed that biogenic AuNPs synthesized from the South African Galenia africana and Hypoxis hemerocallidea plants extracts showed that there was no significant reduction in viability of KMST-6 cell after 24 h treatment with AuNPs with concentrations up to 32 nM [ 16 ]. The same finding has been demonstrated by Patra [ 67 ], showing that AuNPs were non-toxic towards Hek293T cells.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the presence of elements such as calcium and potassium can be due to the micronutrients in the TM extracts used in the synthesis. The weak signals for oxygen in the spectra may have originated from the biomolecules bound to the surface of the NPs [ 52 ], Cu from the support HRTEM grid and film and Co from the lenses of the microscope [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of ZP is therefore, a subject of repulsion and attraction that has been used to estimate how long the nanoparticle dispersions would remain stable. The negative zeta-potential values obtained for the Au NPs fall in the range that is typical of stable colloidal dispersions [72]. The ZP measurement for the nanomaterials was repeated on the seventh day through to the fourteenth day showing only slight changes.…”
Section: Dynamic Light Scattering (Dls) Measurement Of Au Npsmentioning
confidence: 95%
“…The method description of [72] was adopted. Slight changes were only in the monitoring period, which was 0, 12 and 24 h. The stability was evaluated as soon as the solutions were mixed with the nanoparticles and after incubation at 37 • C.…”
Section: Stability Studymentioning
confidence: 99%